2019
DOI: 10.1038/s41467-019-11983-3
|View full text |Cite
|
Sign up to set email alerts
|

Na+-H+ exchanger 1 determines atherosclerotic lesion acidification and promotes atherogenesis

Abstract: The pH in atherosclerotic lesions varies between individuals. IgE activates macrophage Na + -H + exchanger (Nhe1) and induces extracellular acidification and cell apoptosis. Here, we show that the pH-sensitive pHrodo probe localizes the acidic regions in atherosclerotic lesions to macrophages, IgE, and cell apoptosis. In Apoe –/– mice, Nhe1-deficiency or anti-IgE antibody reduces atherosclerosis and blocks lesion acidificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Finally, NHE1 hyperactivity has recently been shown to be involved not only in the onset of cancer all along the digestive tract, from the degeneration of Barret’s esophagus into esophageal cancer to the relationship of inflammatory bowel disease and colon cancer, but also in the onset and promotion of atherosclerosis. This latter feature makes a hyperactive NHE also highly important outside the oncological setting [ 57 , 58 , 59 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The mentioning
confidence: 99%
“…Finally, NHE1 hyperactivity has recently been shown to be involved not only in the onset of cancer all along the digestive tract, from the degeneration of Barret’s esophagus into esophageal cancer to the relationship of inflammatory bowel disease and colon cancer, but also in the onset and promotion of atherosclerosis. This latter feature makes a hyperactive NHE also highly important outside the oncological setting [ 57 , 58 , 59 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The mentioning
confidence: 99%
“…Deficiency of TLR4 protected mice from Ang‐II perfusion‐induced AAA . We recently showed that Nhe1‐deficiency also reduced diet‐induced atherosclerosis and Ang‐II perfusion‐induced AAA formation in mice (Shi, unpublished observation). We showed that IgE activities in activating foam cell formation and associated signaling transduction (p‐AKT, p‐PI3K, and p‐mTOR), and in inducing protease expression and apoptosis were blocked in macrophages from Apoe −/− Nhe1 +/− mice .…”
Section: Discussionmentioning
confidence: 99%
“…We showed that IgE activities in activating foam cell formation and associated signaling transduction (p-AKT, p-PI3K, and p-mTOR), and in inducing protease expression and apoptosis were blocked in macrophages from Apoe −/− Nhe1 +/− mice. 28 IgE-induced macrophage expression of IL6 and monocyte chemoattractant protein-1 (MCP-1) and macrophage apoptosis were also muted in cells from TLR4-deficient Tlr4 −/− mice. 27 Therefore, the activities of TLR4 and Nhe1 may also be affected in Fcεr1a −/− mice, thereby contributing to reduced AAA in these mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations